Fixation Of Diaphyseal Fractures Of Femur Using Kuntschers Nail With Supplementary Fixation Is It Still Relevant? - Verma, Dr A; Jain, Dr V K (International Journal of Innovative Research in Medical Science, 2016)
Femoral nailing has advanced continuously over the past 60 years. The transition from open nailing techniques to closed techniques using a remote entry site at the proximal femur paralleled the availability of image intensifiers and specialised equipment and centres. The introduction and increased popularity of interlocking nails allowed for improved rotational control, better maintenance of femoral length, early weight bearing, the use of smaller implants, and improved control of comminuted and segmental fractures.Today interlock nailing has become the gold standard for diaphyseal fractures of femur all over the world but even in today’s world there exist a large chunk of population who cannot avail of these methods. In a developing country like India the availability of such techniques and facilities is largely limited to urban centres only; while the majority of the population of the rural areas are unaware or unable to avail them. Many factors are responsible for this scenario like lack of facilities (equipments and trained manpower) in the local area, lack of proper maintenance of equipment if available, lack of proper transport facility to an equipped centre and economic constrains. This results in such a major fracture being treated by herbal treatment/ quacks/ osteopaths or not being treated at all causing great morbidity and mortality. In such a scenario the use of retrograde Kuntschers nailing with supplementary screw/plate fixation offers a viable alternative giving acceptable results at a fraction of the cost and being possible in any operation theatre using the basic orthopaedic instruments and techniques.We retrospectively reviewed the results of 110 cases of femoral diaphyseal fractures treated by retrograde Kuntschers nailing with supplementary screw/plate fixation from June 2004 to December 2010.